End-Stage Renal Disease-Associated Gut Bacterial Translocation: Evolution and Impact on Chronic Inflammation and Acute Rejection After Renal Transplantation - Carron, Clémence; Pais de Barros, Jean-Paul; Gaiffe, Emilie; Deckert, Valérie; Adda-Rezig, Hanane; Roubiou, Caroline; Laheurte, Caroline; Masson, David; Simula-Faivre, Dominique; Louvat, Pascale; Moulin, Bruno; Frimat, Luc; et al. (Frontiers in Immunology, 2019)
Chronic inflammation in end-stage renal disease (ESRD) is partly attributed to gut bacterial translocation (GBT) due to loss of intestinal epithelium integrity. Increased levels of circulating lipopolysaccharide (LPS) –a surrogate marker of GBT– contribute to maintain a chronic inflammatory state. However, circulating LPS can be neutralized by lipoproteins and transported to the liver for elimination. While ESRD-associated GBT has been widely described, less is known about its changes and impact on clinical outcome after kidney transplantation (KT). One hundred and forty-six renal transplant recipients with serum samples obtained immediately before and one year after transplantation (1-Year post KT) were included. Intestinal epithelium integrity (iFABP), total LPS (by measuring 3-hydroymyristate), LPS activity (biologically active LPS measured by the LAL assay), inflammatory biomarkers (sCD14 and cytokines), lipoproteins and LPS-binding proteins (LBP and phospholipid transfer protein [PLTP] activity) were simultaneously measured. At 1-Year post KT, iFABP decreased but remained higher than in normal volunteers. Total LPS concentration remained stable while LPS activity decreased. Inflammation biomarkers decreased 1-Year post KT. We concomitantly observed an increase in lipoproteins. Higher sCD14 levels before transplantation was associated with lower incidence of acute rejection. Although GBT remained stable after KT, the contemporary increase in lipoproteins could bind circulating LPS and contribute concomitantly to neutralization of LPS activity, as well as improvement in ESRD-associated chronic inflammation. Chronic exposure to LPS in ESRD could promote endotoxin tolerance and explain why patients with higher pre-transplant sCD14 are less prompt to develop acute rejection after transplantation.